Organizational Justice and its Impact on Achieving Marketing Prowess: Analytical Study in Samawah Cement Factory - Kadim, Jasim Rahi; Sabti, Yousif Mousa; Ali , Ghazanfar; Shliot, Sadeq Mehdi (South Asian Journal of Social Sciences and Humanities, 2021)
The current research chose the dimensions of organizational justice (distributive justice, procedural justice, interactive justice) and exclusion marketing prowess these are exploring opportunities, exploiting opportunities, and marketing flexibility. The purpose of the research was to test the possibility of organizational justice contributing to achieving marketing prowess. And standing at the level of both organizational justice and marketing prowess, and from here it becomes clear to us its importance. And by searching for the problem through a group of questions centered on whether there is a correlation and influence between the research variables, and in light of this, a hypothetical model was constructed from which the main and sub-research hypotheses emerged. To test the validity of the hypotheses, the data were collected through the questionnaire tool, and it was prepared for this purpose. A sample represented the size of (40) workers in the researched laboratory. The data were analyzed using a set of statistical methods and the results were extracted using the computer program (v.16 SPSS), and in light of the results and analyzes, the research reached a set of conclusions, including the decrease in workers ’sense of fairness of wage distribution procedures. And rewards for workers would cause the worker to lose the performance evaluation criteria, and to separate the goals of the worker from the goals of the organization. Finally, the research presented a set of recommendations, which is the necessity of setting fixed standards for each department in the laboratory to work so that the worker can, through these criteria, evaluate his performance and know his duties and rights. Also, laboratory management must take care to involve all workers in making decisions that affect their work, which contributes to making these decisions more effective.